Assessment of MgZr4P6O24 as a Solid Electrolyte for Sensing Mg in Molten Non-Ferrous Alloys. Issue 2 (28th January 2020) - Adamu, Mohammed; Jacob, K. T.; Kale, Girish M.
Abstract : The potential solid electrolyte, MgZr4 P6 O24 was prepared using a modified sol-gel method. Both structural and electrical properties of the solid electrolyte were determined. DSC-TGA analysis indicated that pure dried xerogel when calcined at 900 °C converts to single phase MgZr4 P6 O24 nanopowder with good crystallinity. Pellets of 13 mm diameter and 3.8 mm thickness made by uniaxial compression were sintered at 1300 °C for 24 h. XRD and HR-TEM indicated that the crystalline phase is monoclinic having crystallite size of approximately 40 nm. The sintered pellets were stable in the temperature range from 1000 to 1300 °C, with minor extraneous peaks indicating traces of a coexistent second phase (Zr2 P2 O9 ) at the higher temperature. Using impedance spectroscopy, the electrical conductivity of MgZr4 P6 O24 was determined as 7.23 × 10 –3 Scm −1 at 725 °C. MgZr4 P6 O24 pellet was successfully used for fabrication of a solid-state Mg-sensor for measuring Mg concentration in molten Al at 700 ± 5 °C, with biphasic powder mixture of MgCr2 O4 + Cr2 O3 as ceramic reference electrode in air. A linear dependence of emf on logarithm of Mg concentration was obtained. The results indicate that the transport number of Mg 2+ -cation in MgZr4 P6 O24 is 0.85 ± 0.03 at 700 °C. The solid electrolyte has likely applications in high-temperature electrochemical sensors.